IDENTIFICATION OF ASCORBIC ACID CONTENT IN Carica papaya L. USING IODIMETRY AND UV-VIS SPECTROPHOTOMETRY - Nosy Maria Riscahyani; Evy Ratnasari Ekawati; Khoirul Ngibad (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
Ascorbic acid mostly comes from vegetables and fruits, especially fresh fruits. Vitamin C is a vitamin that can be formed by several types of plants. One of them is papaya which has various contents including vitamin C that can increase endurance, help skin rejuvenation and repair body tissues. The purpose of this study was to determine the levels of vitamin C contained in papaya using iodimetry and UV-Vis spectrophotometry. The sample used in this study was papaya fruit. Determination of vitamin C levels in papaya samples using the titration method bas done by adding sample filtrate with starch indicator then titrated with titrant I2 until the endpoint color of blue titration is formed. Other hands, the determination of vitamin C levels in papaya samples using the UV-Vis spectrophotometry method bas conducted by making an ascorbic acid calibration curve then the filtrated sample was added with H2SO4 5% and ammonium molybdate reagent, then the absorbance of the sample was measured at 494 nm wavelength. The results of the determination of vitamin C levels using the iodimetry was 0.0147% and the results of the determination of vitamin C levels using the UV-Vis spectrophotometry method was 0.1313%. In conclusion, vitamin C levels analyzed by using UV-Vis spectrophotometry methods were greater than vitamin C levels analyzed by using the iodimetry method.